2007
DOI: 10.1007/s11434-007-0248-3
|View full text |Cite
|
Sign up to set email alerts
|

Single grain Rb-Sr dating of euhedral and cataclastic pyrite from the Qiyugou gold deposit in western Henan, central China

Abstract: The Rb-Sr isotopic dating of pyrite mineral from ore deposits can directly provide mineralization age. However, many geological factors may affect the Rb-Sr isotopic system, which baffles application of this method. Employing ultra-low procedural blank Rb-Sr method, we have dated pyrites separated from the No. 4 breccia pipe of the Qiyugou gold deposit, western Henan Province. Single grains of euhedral pyrite crystal with few micro-cracks yield an isochron age of 126 ± 11 Ma, which represents time of the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Except the enrichment of Te in the Songligou gold‐telluride deposit, Te‐rich hydrothermal fluid played an important role in the Xiaoqinling‐Xiong'ershan district from Late Triassic to Early Cretaceous, which indicated that there could be an enriched source of Te in this district. Tellurides were not only found in Late Cretaceous gold deposit, for example, Qiyugou (Shao & Luan, ; Wang et al, ; Han et al, ), Yangzhaiyu (Li et al, ; Jian et al, ), Wenyu (Li et al, ; Zhao et al, ), and Fancha (Li et al, ; Ren, ) gold deposit. Besides, tellurides were also found in the Early Cretaceous Jinduicheng porphyry Mo deposit (Stein, Markey, Morgan, Du, & Sun, ; Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Except the enrichment of Te in the Songligou gold‐telluride deposit, Te‐rich hydrothermal fluid played an important role in the Xiaoqinling‐Xiong'ershan district from Late Triassic to Early Cretaceous, which indicated that there could be an enriched source of Te in this district. Tellurides were not only found in Late Cretaceous gold deposit, for example, Qiyugou (Shao & Luan, ; Wang et al, ; Han et al, ), Yangzhaiyu (Li et al, ; Jian et al, ), Wenyu (Li et al, ; Zhao et al, ), and Fancha (Li et al, ; Ren, ) gold deposit. Besides, tellurides were also found in the Early Cretaceous Jinduicheng porphyry Mo deposit (Stein, Markey, Morgan, Du, & Sun, ; Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…From west to east, four primary NE‐trending faults, namely, the Tieluping Fault, Kangshan‐Shanggong Fault, Hongzhuang‐Qinggangping Fault, and Taocun‐Maoyuan Fault, and the EW‐trending Machaoying Fault control the distribution of lode gold deposits in this region. Besides, the Qiyugou gold deposit (126 ± 11 Ma, Han, Li, Zhang, Zhang, & Chen, ; 125–115 Ma, Wang, Mao, & Lu, ) is regarded as an intrusion‐related cryptoexplosion breccia pipe‐type gold deposit (Chen, Pirajno, Li, Guo, & Lai, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rb-Sr isotopic dating of ore sulfides represents a direct way to determine the hydrothermal mineralization age (Nakai et al, 1993;Nebel et al, 2011). With the advance of high-precision mass spectrometry with low detection limit, the technique is now widely applicable in dating hydrothermal minerals (Cao et al, 2015;Hu et al, 2015;Yang et al, 2017) such as sphalerite (Ostendorf et al, 2015;Rosa et al, 2016) and pyrite (Yang & Zhou, 2001;Han et al, 2007;Li et al, 2008;Wang et al, 2014c). The fact that 87 Sr/ 86 Sr ratios do not vary with 1/Sr values (Fig.…”
Section: Timing Of the Pb-zn Mineralizationmentioning
confidence: 99%
“…Single mica grains (i.e., detrital muscovite and biotite) were used for Rb-Sr dating. The single-grain or microsample technique was recently developed and, so far, has been explored for dating micas from magmatic and metamorphic rocks (Müller et al, 2000a, b;Li et al, 2005), sulfide minerals from ore deposits (Li et al, 2008a;Han et al, 2007), and foraminifera from marine sediments (Tong et al, 2006). In the present study we show that the single-mica grain Rb-Sr analytical technique is a potential tool to study the origin of detrital minerals and the provenance of geological terranes.…”
Section: Introductionmentioning
confidence: 99%